Dermoscopic features in relation to the type of clinical lesions in cutaneous leishmaniasis - Qasim S. Al Chalabi; Hala N. Al Salman; Anfal L. Al harbawi (Journal of the Egyptian Women’s Dermatologic Society)
Background Cutaneous leishmaniasis (CL) is an endemic disease in our region. Early management of the disease is crucial to control the spread of the disease and prevent complications. Objective To determine the dermoscopic characteristics of CL lesions and their relation with the clinical types. Patients and methods Ninety-three patients (248 lesions) were enrolled in this cross-sectional study. Each lesion was examined using a dermatoscope after confirming the diagnosis of CL by a slit smear and direct identification of the parasite by Giemsa-stained slides using a light microscope. The data were recorded, analyzed, and tabulated. Results A total of 124 noduloulcerative, 83 plaques, 20 papules, 13 nodules, and eight ulcerative lesions were included in this study, the limbs were the most frequently affected site (210 lesions). Diffuse background erythema was found in all lesions, in 97 lesions the erythema was dusky red, light red in 145 lesions, and yellowish red in six. Most lesions (76.2%) had hyperkeratosis with central erosion and ulceration. Yellow tears (103 lesions) were the most common dermatoscopic finding, they were observed more commonly in nodular and noduloulcerative lesions (P value <0.05). The next common dermatoscopic signs were a white star-burst-like pattern (41 lesions) and salmon-colored ovoid seen in 37 lesions, both of them seen more frequently in nodular and noduloulcerative lesions (P value <0.05). Vascular structures (232 lesions) were more prevalent in nodular and noduloulcerative lesions (P value <0.05). The most frequent vascular signs were linear irregular vessels in 69 lesions, followed by comma-shaped vessels in 51, and dotted in 48 lesions. Conclusion Yellow tears, white starburst-like pattern, and salmon-colored ovoid structures were the most frequent dermatoscopic signs observed and were significantly associated with nodular and noduloulcerative type, limbs were the most common affected site. Linear irregular, comma-shaped, and dotted vessels were the most frequent vascular pattern in nodular and noduloulcerative lesions. Therefore, these signs with the clinical examination might help dermatologists to diagnose CL in endemic regions.